Answer : The correct option is, (B) Step 2
Step-by-step explanation :
The given expression is:
3(x - 2) = 3
In this expression, 'x' is a variable.
By using distributive property, we get:
3x - 6 = 3
Now adding 6 on both side, we get:
3x - 6 + 6 = 3 + 6
Now combining like terms, we get:
3x = 9
Now dividing the expression by 3, we get the value of 'x'.
x = 3
The meaning of like terms in mathematics is that have the same variables and exponents.
Hence, the step result of combining like terms is, Step 2